Peningkatan Produksi Tanaman Kentang (Solanum tuberosum L.) dengan Menggunakan Kompos Kipahit (Tithonia diversifolia) dan Pupuk Kandang Ayam - Etimanta Pratama Sembiring; Maria Marina Herawati (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2024)
This research aims to determine the effect of compost from kipahit plants and chicken manure as organic material on increasing potato growth and productivity, as well as to find out the best fertilizer among kipahit plant compost, chicken manure, and the combination of kipahit with chicken coop on growth and potato crop productivity. The research method used in this research is a type of experimental research with a design prepared in a Randomized Group Design (RAK). Growth variables are seen from plant height, number of leaves, leaf area, and chlorophyll content. Meanwhile, productivity variables are measured by the number of tubers per plant (seeds), tuber weight per plant, and shoot dry fruit weight. The results of the research showed that there was an effect of providing compost fertilizer on plant growth and productivity (sig < 0.05), with the highest results from measuring the growth and productivity of potato plants for all variables being the application of compost fertilizer from kipahit and chicken manure. In conclusion, there is an influence of compost fertilizer on the growth and productivity of potato plants, with the best fertilizer being a combination of chicken manure and kipahit. Keywords: Chicken coop, Growth, Productivity, Kipahit Compost Fertilizer, Potato Plants